Omicron infection-associated T- and B-cell immunity in antigen-naive and triple-COVID-19-vaccinated individuals - Barros-Martins, Joana; Hammerschmidt, Swantje I.; Morillas Ramos, Gema; Cossmann, Anne; Hetzel, Laura; Odak, Ivan; Köhler, Miriam; Stankov, Metodi V.; Ritter, Christiane; Friedrichsen, Michaela; Ravens, Inga; Schimrock, Anja; et al. (Frontiers in Immunology, 2023)
Since early 2022 various Omicron variants dominate the SARS-CoV-2 pandemic in most countries. All Omicron variants are B cell immune escape variants and antibodies, induced by first generation COVID-19 vaccines or infection with earlier SARS-CoV-2 variants, largely fail to protect individuals from infection. In the present study, we investigated the effect of Omicron infections in triple vaccinated as well as in antigen-naïve individuals. We show that Omicron breakthrough infections occurring 2 to 3.5 months after the third vaccination reconstitute B cell and T cell immune responses to levels similar or above those measured 14 days after the third vaccination including induction of Omicron-neutralizing antibodies. Antibody responses in breakthrough infection derived mostly from cross-reacting B cells initially induced by vaccination, whilst Omicron infection in antigen-naïve individuals generated primarily B cells binding to the Omicron but not the Wuhan spike protein. Although antigen-naïve individuals mounted profound T cell responses after infection, B cell responses were low and neutralizing antibodies were frequently below the limit of detection. In summary, the detection of Omicron-associated B cell responses in primed as well as antigen-naïve individuals supports the application of Omicron-adapted COVID-19 vaccines, but questions their suitability if they also contain/encode for antigens of the original Wuhan virus.